(untitled) (Archive of Conferences, 2021)
In this paper, the process of technology education in secondary schools in general the fact that the use of electronic-didactic tools and the use of modern information technologies are one of the most important tasks in the preparation of students for technology, and the formation of students as a free-thinking, independent, creative person, is given information